Guatemala: The impact of covid-19 and other shocks, and policy implications: Final report - Díaz-Bonilla, Eugenio; Flores, Luis; Piñeiro, Valeria; Centurión, Miriam (International Food Policy Research Institute, 2022)
Two previous reports (Díaz Bonilla, Laborde and Piñeiro, 2021, and Diaz-Bonilla, Flores, Paz, Piñeiro, and Zandstra, 2021) covered the evolution and impacts of the pandemic on food systems in Guatemala until the time of their writing (which together covered from the start of the pandemic in early 2020 until about October 2021. This third report concludes the analysis of the impact of the COVID-19 pandemic on food systems in Guatemala. It summarizes the previous reports and updates the analysis until the end of May 2022. However, this country and its food systems have also been affected by other events since the pandemic started in early 2020. Between 3 and 17 November 2020, tropical storms Eta and Iota hit Guatemalan territory with heavy rains that led to floods and mud landslides, affecting 16 of the country's 22 departments. Later, in 2021 the strong world economic rebound due to expansionary fiscal and monetary policies in the USA and many other developed and developing countries combined with persistent strains on value chains due to COVID19 to lead to increases in transportation costs and the prices of food, energy, and fertilizers. In the case of agricultural products, those increases were com-pounded by adverse climate events in some important producers, particularly in South America. Finally, the Russian-Ukraine Conflict (RUC) on February 24, 2022, has added further pressures on the prices of energy, fertilizers and food products including wheat and vegetable oils. Therefore, the pandemic's specific impact on Guatemala's food systems has been interacting with the other developments mentioned, making it very difficult to differentiate among them. Policymakers, how-ever, need to respond to the overall impact of the conditions affecting the population, whatever the leading causes may be. Therefore, this final report, while emphasizing those aspects linked to the pan-demic, will discuss the conditions in Guatemala considering those other factors. This report is structured as follows. First, it summarizes the main policy responses, costs, and financing related to the COVID-19 shock. Second, it brings up to date the evolution of the pandemic, using differ-ent indicators. Third, it updates the evolution of key economic and nutritional variables. Fourth, there is a brief discussion of the implications of RUC for food systems.. Fifth, the report continues with a more specific analysis of the evolution of some food value chains that are central for food consumption in Guatemala. The next section discusses policy considerations for health, poverty and nutrition, and food value chains, based on the updated analysis of the previous sections, including cost and financial as-pects. A final section concludes.